The Role of Mediator Communication in Symbolic Interaction of Divorce Mediation at The Sidoarjo Religious Court - Adinda Samudra; Nihayatur Rohmah; Camellia Khairul (Journal of Religion, Local Politics, and Law, 2026)
This study examines the role of symbolic interactionism in divorce mediation, focusing on how mediators at the Sidoarjo Religious Court construct and communicate the concept of a “harmonious family” through symbolic interactions. The research responds to rising divorce rates in Indonesia, particularly in Sidoarjo, where emotional conflict and poor communication often hinder mediation. Using a qualitative case study approach, data were collected through participatory observation, in-depth interviews, and documentation. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Research subjects consisted of court mediators and divorcing couples selected purposively based on experience and relevance. The findings show that mediators facilitate dialogue through verbal and nonverbal symbols such as empathy, adaptive language, polite greetings, and friendly gestures. Mediators also reinterpret the idea of a harmonious family from a hierarchical model toward one based on equality, mutual understanding, shared responsibility, and child welfare, supported by moral and religious advice. This study concludes that mediation functions not only as a legal process but also as a space for social and moral learning, emphasizing the importance of communication skills in achieving peaceful and sustainable resolutions.